The Contribution of Inservice Teacher Education Program (PPG) on Teachers' Professionalism - Basikin, Basikin (English Language Teaching Educational Journal, 2023)
Teacher professional development (TPD) programs have been considered an inportant aspect in teacher development and quality improvement. They are believed to be able to improve teachers’ knowledge and skills which in turn improve students’ learning and improvement. This study examined the contribution of a TPD program for English teachers, PPG in Indonesia on the teacher professionalism, particularly their beliefs about good English teaching, knowledge and skills in English teaching, and practices in the classrom teaching. Data were collected through a close-ended survey, observation, and reflectice interviews with online-inservice PPG techear alumni. Findings suggested that although teacher participants reported that PPG contributed to changes in their beliefs about better English teaching and knowledge and skills in teaching English, such chnages were not reflected in their teaching practices. Such findings implied an improvement of the PPG program structure to include support provided toi teachers when they implement the knowledge and skills in the classrooms.